Penerapan Sistem Pakar pada Diagnosa Penyakit Tanaman Karet dengan Metode Forward Chaining (FC) - Nazira Ayu Ananda; Eka Irawan; Muhammad Ridwan Lubis; M Safii (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The study aimed to analyze rubber plant diseases using expert system techniques. Sources of data obtained from PT. Bridgestone Jl. Dolok Merangir Satu, Simalungun Regency by conducting observations and interviews with PT. Bridgestone. The presence of several diseases in rubber plants can make PT. Bridgestone incurs losses, so it needs proper handling. The solution given is the Forward Chaining (FC) method, which is part of an expert system so that a more efficient solution is to detect diseases in rubber plants. The results of the study indicate that the analysis can be carried out using the FC method in the diagnosis of rubber plants by implementing it into a web-based programming language so that the company can detect rubber plant diseases based on the symptoms given and find out solutions to overcome diseases in rubber plants.